2016
DOI: 10.15294/jbat.v5i1.5965
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PENAMBAHAN ASAM SITRAT TERHADAP KARAKTERISTIK FILM PLASTIK BIODEGRADABLE DARI PATI KULIT PISANG KEPOK (Musa acuminata balbisiana Colla)

Abstract: Kulit pisang dapat digunakan sebagai bahan baku pembuatan film plastik biodegradable karena kulit pisang mengandung pati. Pati yang berasal dari kulit pisang ini cepat berubah warna atau mengalami browning. Hal ini dicegah dengan penambahan asam sitrat selama proses ekstraksi pati dari kulit pisang. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh penambahan asam sitrat terhadap karakteristik, khususnya kuat tarik dan kemampuan biodegradasi film biodegradable yang terbuat dari pati kulit pisang (FPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 1 publication
0
11
0
4
Order By: Relevance
“…4 Several studies have been reported on the utilisation of starch from various sources such as corn, yam, pea starch, cassava starch, banana peel and sorgum to synthesise coatings and films. [5][6][7][8][9][10] Starch is a polymer type of polysaccharide that has an important role in the manufacture of biodegradable films since it has the easy nature of forming a continuous matrix and its abundant availability in nature, hence it is appropriate if various starch sources are explored for the synthesis of edible film. 5 One potential source of starch is sorghum, which contains 72% starch.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several studies have been reported on the utilisation of starch from various sources such as corn, yam, pea starch, cassava starch, banana peel and sorgum to synthesise coatings and films. [5][6][7][8][9][10] Starch is a polymer type of polysaccharide that has an important role in the manufacture of biodegradable films since it has the easy nature of forming a continuous matrix and its abundant availability in nature, hence it is appropriate if various starch sources are explored for the synthesis of edible film. 5 One potential source of starch is sorghum, which contains 72% starch.…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu syarat karakteristik plastik yang baik yaitu harus memiliki kekuatan tarik serta perpanjangan yang baik. Uji kuat tarik merupakan salah satu uji untuk mengetahui ketahanan suatu bahan terhadap gaya tarik yang dikenakan [8]. Pada Tabel 1 terlihat dimana pada setiap variabel penambahan nilai kuat tarik terus mengalami kenaikan dengan titik tertinggi pada penambahan jumlah kalsium silikat sebanyak 6% menghasilkan nilai kuat tarik 9,56 MPa tetapi mengalami penurunan pada variabel 8% menurut Udjiana [3] hal ini disebabkan karena kalsium silikat yang dicampurkan belum homogen, sehingga penambahan filler yang semakin banyak menghasilkan properties yang berbeda dengan tren sebelumnya dan juga dapat disebabkan karena kalsium silikat yang digunakan belum mencapai ukuran nano.…”
Section: Uji Kuat Tarikunclassified
“…The addition of CMC serves as a filler that can increase the tensile strength of bioplastics. According to Hardjono (2016), states that bioplastics with the addition of CMC will increase the intensity of OH carboxyl groups and have an impact on increasing the tensile strength of bioplastics.…”
Section: Making Bioplasticmentioning
confidence: 99%
“…The more concentrations of CMC added cause more water to be absorbed and bound, which results from CMC being hygroscopic (Rahayu, 2016). Because of its hygroscopic nature, bioplastics with the addition of CMC have high humidity, high humidity levels are a good habitat for microbes to degrade bioplastics (Hardjono et al, 2016). Thus the ability of biodegradation tends to increase with increasing levels of CMC added.…”
Section: Biodegradation Testmentioning
confidence: 99%